Integrating Moderation within the Immoderate-Labelled Islamic Movement (A Case Study of the Personal Experience and Al-Guroba Da'wah Initiatives) - Marheni, Cut Linda; Zumadil, Zumadil (El-Wasathy: Journal of Islamic Studies, 2025)
This research investigates the dynamics of Islamic movements in the setting of religious understanding in Central Aceh, Indonesia. This is carried out by a case investigation, based on the private experiences of an individual and the establishment and the growth of the Al-Guroba dakwah initiative headquarters. By doing an in-depht interview, we examined the evolution in the religious understanding of a figure exposed to various religious histories; from traditional institutions, Salafism, to a more moderate religious thought. This study underscores how trans-national support; ideologically and financially, contributes to the dissemination of fundamentalist Salafism, which often leads to "upheaval" and societal disputes at the local level, as a results of what considered exclusive and less moderate da'wah methodology. The aftermath, Al-Guroba da'wah headquarters evolved and positioned itself as a substitute da'wah movement, practicing an inclusive da'wah. Dakwah is applied through social activities, education, and media. These findings offer perspectives into the evolution of an individual religious understanding, the challenges of pluralism, and the significance of community initiatives in fostering moderation within the various Islamic movement in Indonesia.